2021
DOI: 10.1101/2021.05.04.21256517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 Mental Health Interventions among Community-based Children, Adolescents, and Adults: A Living Systematic Review of Randomised Controlled Trials

Abstract: Background: Scalable interventions to address COVID-19 mental health are needed. Our objective was to assess effects of mental health interventions for community-based children, adolescents, and adults. Methods: We searched 9 databases (2 Chinese-language) from December 31, 2019 to March 22, 2021. We included randomised controlled trials with non-hospitalised, non-quarantined participants of interventions to address COVID-19 mental health challenges. We synthesized results descriptively but did not pool quant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Bonardi et al ( 2021 ) performed a review of nine randomised controlled trials (RCTs). Three were designed during the COVID-19 pandemic and included a racially and ethnically diverse sample.…”
Section: Resultsmentioning
confidence: 99%
“…Bonardi et al ( 2021 ) performed a review of nine randomised controlled trials (RCTs). Three were designed during the COVID-19 pandemic and included a racially and ethnically diverse sample.…”
Section: Resultsmentioning
confidence: 99%
“…Further theoretical and empirical research on how to foster resilience have been formulated (He et al, 2020; Rieckert et al, 2021; Sakurai & Chughtai, 2020). A wide spectrum of evidence-based interventions has been shown effective in improving emotional coping and social support and reducing mental health problems for individuals and communities (Bonardi et al, 2021; Shaygan et al, 2021). However, other interventions have been found to be harmful, so it becomes ever more pertinent to ensure there is appropriate evidence for an intervention’s effectiveness in the context of the pandemic prior to recommending it (Vukčević Marković et al, 2020).…”
Section: Responding To Heterogeneous Situations and Building Resiliencementioning
confidence: 99%
“…Currently, high quality studies on the impact of virtual psychosocial interventions to prevent or treat mental health distress and eating disorders in patients with obesity during COVID-19 remain limited. Reviews to date, including a living systematic review of randomised controlled trials (RCTs), identified that self-guided internet-based cognitive behavioural therapy (CBT) and a layperson supportive telephone intervention improved mental health distress in non-bariatric populations 15 16. Despite this preliminary evidence for virtual mental health interventions during COVID-19 in general and non-bariatric specific populations, these reviews did not identify any interventions that specifically addressed psychological distress or disordered eating in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%